Diabetic Retinopathy Evidence-Based Management - Browning, David J. (Springer New York : Imprint: Springer, 2010)
The field of diabetic retinopathy has changed dramatically in the past five years with the use of intravitreal injections, the incorporation of optical coherence tomography in practice, and the changing importance of fluorescein angiography. Diabetic Retinopathy: Evidence-Based Management provides an up-to-date, evidence-based approach to managing the range of clinical problems encountered by ophthalmologists in patients with diabetic retinopathy. Exposition is grounded with clinical examples, and questions and discussions encourage thinking about problematic situations and areas of controversy. The text also incorporates a wealth of information arising from publications of the Diabetic Retinopathy Clinical Research network, highly illustrated and annotated with supporting evidence. The text can be used by practitioners stimulated by a clinical encounter, or as the basis of linear study within the context of a course. The increasing frequency of diabetic patients in ophthalmic practice makes Diabetic Retinopathy: Evidence-Based Management a timely and practical reference for ophthalmologists and retina specialists.